Load detection of 2D structure using NDT scanning technique - Liu, Jialin (2016)
Avoiding any form of engineering structural failure is crucial for human habitation which may lead to economic loss and could be life-threatening. Ensuring structural safety under in-service conditions is an essential mission. As a result, structural health monitoring (SHM) came into being. SHM refers to the process of the identification of defects in the structure to either repair or abandon for the new structure. SHM has been commonly utilized several traditional methods in the past, such as knocking the structure and listening to output sound for determining the health condition. Nowadays, SHM using smart materials by non-destructive testing is mainly investigated. Modern SHM techniques are developed as automatic periodic inspection systems to detect defects at the earliest. Many researchers devoted to several areas to develop different methods to achieve effective SHM. In this study, wave propagation method based SHM was carried out. Studies were conducted for 1-D and 2-D structures for localization of objects placed at various locations by laboratory tests. Piezoelectric actuator generates lamb wave, which propagates to acquire information of the host structure through piezoceramic sensor. Statistical analysis was conducted to extract information from the output data. Statistical indicators that present the damage/load severity were compared for various experiments by changing the distance between actuator and sensors. Finally, relationships between loading condition and output data were found out. Procedures to identify an unknown load acting on a structure by obtaining waveform using several pair of piezoelectric transducers was illustrated.